Study on the combined action of the entomopathogenic bacterium Bacillus thuringiensis subsp. kurstaki and the entomopathogenic nematode Heterorhabditis bacteriophora - Zampara, I.; Zamparas, C.; Mantzoukas, S.; Karanastasi, E. (ENTOMOLOGIA HELLENICA, 2014)
The interaction between the entomopathogenic bacterium Bacillus thuringiensis subsp. Kurstaki and the entomopathogenic nematode Heterorhabditis bacteriophora (Heterorhabditidae) was examined against larvae of Ephestia kuehniella (Lepidoptera: Pyralidae) at 7, 14, 21 and 28 days post treatment, in laboratory conditions. Three different combinations of the aforementioned pathogens were tested on 4th instar larvae, namely 500ppm B. thuringiensis subsp. kurstaki (B.t.k.) and H. bacteriophora infective Juveniles (1000IJs/ml), 1500ppm B.t.k. and H. bacteriophora (1000IJs/ml) and 3000ppm B.t.k. and H. bacteriophora (1000IJs/ml). At 7, 14 and 21 days, the interaction between the pathogens was additive in two of the treatments and synergistic in one, whereas at 28 days, it was negative in two of the treatments and synergistic in one. Overall, the application of the lowest dose of B.t.k. (500ppm) in combination with H. bacteriophora (1000IJs/ml), turned out to be highly effective. The interaction between B. thuringiensis and H. bacteriophora is to be further examined.